Fixed Point Theorems for Monotone Caristi Inward Mappings. (27th July 2018) - Alfuraidan, Monther Rashed; Jorquera, Eduardo Daniel; Khamsi, Mohamed Amine
Abstract: In this paper, we introduce the monotone Caristi inward mappings. As an example, we show that monotone inward contraction mappings are monotone Caristi inward mappings. A general fixed point theorem for such mappings is given. A mutlivalued version of these results is also introduced.